Creación de una empresa productora y comercializadora de vinos en la ciudad de Santa Marta - Galvis Castro, Francisco José (Universidad Antonio Nariño, 2021)
This project aims to contribute to the agroindustrial development of Magdalena, especially Santa Marta, giving better use of the grapes, with the aim of improving the source of income and creating wines. This product, which is in the process of being harvested, tropical fruit wines have begun to enter the regional and national market, allowing it to compete with brands and manufacturers of other tropical fruit wines, offering consumers a product that guarantees flavor, odor , color and sanitary conditions suitable for human consumption.